PERSONS APPLYING FOR A PSYCHOLOGICAL CONSULTATION - Khaitova Dilafruz Yusupovna (Academia Science Repository, 2023)
This article presents a study on psychological consultations and their effectiveness for individuals seeking help. The study utilized a mixed-methods approach, including qualitative interviews and quantitative surveys, to gather data from participants. The results indicated that psychological consultations can have a positive impact on individuals' mental health and well-being. The article concludes with recommendations for improving psychological consultation services.